In‐site investigation of regional outburst prevention in coal roadway strip of a deep mine using an improved method. Issue 11 (30th June 2020) - Yang, Huiming; Wang, Zhonghua; Zhang, Yongjiang; Cao, Jianjun; Liu, Yanbao; Yang, Xuelin; Li, Chengcheng
Abstract: With the increase of mining depth, the occurrence mechanism of coal and gas outburst becomes more complex, and stress‐dominated outburst disaster has become one of the major safety problems in deep coal mines. Therefore, stress relief of coal seam has become an urgent technical demand for outburst prevention method in deep mines. In this study, based on zonal disintegration characteristics of deep surrounding rock, a regional strip outburst prevention method, called strip stress relief combined with gas extraction through stress‐relief floor roadway, was proposed, and relevant in‐site investigations were carried out in the Qujiang coal mine in China. Our results show that the zonal disintegration phenomenon occurs in the high‐stress surrounding rock at great depths, and induces the stress‐relief effect on the upper coal seam, in which the permeability and extraction radius of boreholes are increased greatly. The results of deformation and failure of surrounding rock of floor roadway show that from the surface to deep regions, fractured and nonfractured zones were alternatively distributed in the surrounding rock of deep floor roadways, the damage degree of surrounding rock was gradually weakened, and the width of fractured area was gradually reduced. The displacement of surrounding rock also presented the characteristics of alternative distribution of wave peak and trough. Moreover, the deformation and failure of surrounding rock presented a time‐dependent rheological behavior. In the stress‐relief zone, the coal seam permeability was enhanced significantly, with the maximum value being 43 times larger than that of the original coal seam. The effective gas extraction radius of the borehole was improved by 15%‐45%. During the driving period of coal roadways, the outburst risk prediction indexes K 1 and S of the working face were lower than the critical value, and the driving speed of the coal roadway improved from 40 m per month to 100 m per month. This indicates that the proposed strip regional outburst prevention method can simultaneously reduce the ground stress and the gas content, and can effectively eliminate the outburst risk of coal roadway in deep mines. Abstract : A regional strip outburst prevention method, called strip‐stress relief combined with gas extraction through a stress‐relief floor roadway, is proposed. The zonal disintegration phenomenon occurs in the high‐stress surrounding rock at great depths and induces the stress‐relief effect on the upper coal seam, in which the permeability and extraction radius of boreholes are increased greatly.